2016
DOI: 10.3892/etm.2016.3951
|View full text |Cite
|
Sign up to set email alerts
|

Different roles of Staphylococcus aureus enterotoxin in different subtypes of nasal polyps

Abstract: Abstract. Chronic rhinosinusitis with nasal polyps (CRSwNP) is a multifactorial disease. The pathogenesis of CRSwNP remains unclear. This study was designed to investigate the role of inflammation and Staphylococcus aureus enterotoxin (SE) in this disease. The study included a total of 74 patients with CRSwNP and 6 controls. A serum Phadiatop assay was conducted to detect atopy status, and serum eosinophil cationic protein (ECP) and total immunoglobulin (Ig)E levels were determined using ELISA. SEA, SEB, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In 100% of patients with aspirin exacerbated respiratory disease (AERD), specific IgE anti SAE [ 25 ] was found in polyp homogenates. In the case of the neutrophilic (non-eosinophilic) endotype of CRSwNP in Chinese population, the concentrations of staphylococcal superantigens and specific IgE are significantly lower than in the case of the eosinophilic endotype of rhinosinusitis, and mainly play the infectious role [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 100% of patients with aspirin exacerbated respiratory disease (AERD), specific IgE anti SAE [ 25 ] was found in polyp homogenates. In the case of the neutrophilic (non-eosinophilic) endotype of CRSwNP in Chinese population, the concentrations of staphylococcal superantigens and specific IgE are significantly lower than in the case of the eosinophilic endotype of rhinosinusitis, and mainly play the infectious role [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human ILC2s, driven by GATA3 [63], can produce at least small amounts of IL-4 [64][65][66][67], and the stimulation of adult human ILC2s with IL-33 in combination with IL-2 or IL-7 induces release of . This may result in increased IgE production without antigen specificity, comprising hundreds of functional IgE specificities and contributing to often very high total tissue IgE levels [48], along with pronounced eosinophilic inflammation (type 2 inflammation) [50,69] The functionality of SE-IgE antibodies from nasal polyp tissue has been repeatedly demonstrated, using mast cell and basophil activation or the promotion of IgE-facilitated allergen binding to B cells (IgE-FAB) [48,70]. Interestingly, in nasal polyps, high concentrations of both IgE and IgG antibodies can be found.…”
Section: Role Of Splsmentioning
confidence: 99%
“…It has been suggested that type 2 inflammation is triggered by S. aureus via Toll-like receptor 2, which is a pattern recognition receptor [ 60 , 61 , 62 ]. Studies have also been shown that the Asian CRSwNP population has more type 2 low inflammation, and CRSwNP tissue of Asian patients present lower superantigen effects [ 63 , 64 ].…”
Section: The Role Of Antibodies In Airway Diseasesmentioning
confidence: 99%